Posterior Müller Muscle-Conjunctival Resection as a First Step to Treat Eyelid Ptosis: Clinical Results and Treatment Algorithm - Fechner, Maarten; Kappen, Isabelle Francisca Petronella Maria; van Rooij, Joep Antonius Franciscus; van der Lei, Berend (Aesthetic surgery journal. Open forum, 2024)
Abstract Background The posterior Müller muscle-conjunctival resection (MMCR) procedure is a straightforward procedure for the correction of eyelid ptosis with a relatively short operating time and fast recovery. Traditionally, its use was limited to patients with mild involutional ptosis and good levator function and a positive phenylephrine test result. Objectives To evaluate the efficacy of the MMCR procedure as a primary step to treat eyelid ptosis with varying etiology and severity, including patients with more severe ptosis and moderate levator function, and to produce a treatment algorithm. Methods A retrospective analysis of the results of 34 patients, comprising 56 operated eyelids, treated with the MMCR procedure for eyelid ptotis between 2016 and 2018, was performed. Preoperative and postoperative pictures were analyzed for determining the margin-to-reflex distance (MRD1), symmetry, and complications. Results We found a mean preoperative MRD1 of 1.3 mm (SD 1.1) and postoperative MRD1 of 3.2 mm (SD 1.0). The mean postoperative MRD1 for unilateral and bilateral cases was 3.4 (SD 0.8) and 3.2 (SD 1.1), respectively. Only 2 patients (5.9%) had an asymmetrical postoperative result (>1.0 mm MRD1 difference), and both were unilateral cases. Complications were scarce: only 1 patient (2.9%) developed dry eyes and 2 patients experienced temporary discomfort from the conjunctival sutures. Conclusions The MMCR procedure appears to be an excellent procedure as a primary step to correct eyelid ptosis with varying etiologies and severity, due to its low risk of asymmetry, short learning curve, and high success rate. A flow chart as treatment algorithm is provided for clinical decision making. Level of Evidence: 4